ANALISIS GAYA BAHASA PUISI SUMPAH ABADI KARYA DEE LESTARI: KAJIAN STILISTIKA - Heru Prasetyo; Siti Asmaul Husna; Ayu Setiyo Putri (FKIP Universitas Lampung, 2021)
Language style in a poem is not only useful as a function of beauty, but also a means to communicate an event. Diction or word choice is raised to present a hidden beauty. This study aims to describe the form of language style that is present in the poem